HAKIKAT MANUSIA DAN IMPLIKASINYA TERHADAP FILSAFAT PENDIDIKAN ISLAM - Alfarizi, Moch Salman; Asy'arie , Musa; Shobahiya, Mahasri; moch salman (LPPM STAI Muhammadiyah Probolinggo, 2026)
The moral and spiritual crisis that occurs in the midst of scientific and technological advances shows that there is an inequality in the modern educational process that emphasizes too much on the intellectual aspect and ignores the spiritual dimension of humans. In the Islamic view, human beings have a complete essence, including elements of the body, intellect, spirit, and nafs that must be developed in a balanced manner. This research aims to analyze the concept of human nature from an Islamic perspective and outline its implications for the philosophy of Islamic education. Using a qualitative approach based on literature study, this study found that human nature is the ontological, epistemological, and axiological foundation for Islamic education. Islamic education is ideally directed to form kamil people through the integration of intellectual, moral, and spiritual development. The implications of this study emphasize that the philosophy of Islamic education must be oriented towards the formation of people who are faithful, knowledgeable, and civilized, so that they are able to answer the challenges of the times while supporting the development of superior human resources and character within the framework of monotheistic values.